2014
DOI: 10.1007/s00417-014-2795-z
|View full text |Cite
|
Sign up to set email alerts
|

A new surgical triple procedure in pseudoexfoliation glaucoma using cataract surgery, Trabectome, and trabecular aspiration

Abstract: The triple procedure is more effective in lowering intraocular pressure compared to phacoemulsification and trabecular aspiration alone in pseudoexfoliation glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…Two compared phaco-AIT with trabecular aspiration and found lower IOPs with phaco-AIT 21 45. An abstract compared 52 phaco-AITs with 49 phacoemulsification procedures where 2 iStents were inserted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two compared phaco-AIT with trabecular aspiration and found lower IOPs with phaco-AIT 21 45. An abstract compared 52 phaco-AITs with 49 phacoemulsification procedures where 2 iStents were inserted.…”
Section: Resultsmentioning
confidence: 99%
“…AIT can be expected to lower the IOP by approximately 36% to a final average IOP around 16 mm Hg. To try to give some type of comparison from the available data, a single iStent has been shown to reduce the IOP by 8%43–27%47 with an overall mean final IOP near 17 mm Hg with significantly greater reductions reported when inserting more than one stent 46. Endoscopic cyclophotocoagulation used for POAG (as opposed to neovascular glaucoma) decreases the IOP by 8%48–47%,49 to a final average near 15 mm Hg.…”
Section: Resultsmentioning
confidence: 99%
“…Steroid glaucoma and pseudoexfoliation often produce very high IOPs and the primary pathology is located in the trabecular meshwork. As a result, ablating the meshwork reduces intraocular pressure very effectively 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature investigating TA in XFG remains limited; however, more recent studies have been conducted in which TA is used in conjunction with or compared with ab interno trabeculectomy with Trabectome. In one retrospective study of 30 patients, a triple surgical procedure of cataract extraction, Trabectome and TA was compared with cataract extraction and TA alone 107. The study found that the triple procedure group had a significantly greater reduction in IOP compared with the control group (38.4% vs 26.8%).…”
Section: Exfoliative Glaucomamentioning
confidence: 99%